Epifauna del ostión espinoso Spondylus princeps unicolor (Mollusca: Bivalvia), de Puerto Escondido, Golfo de California, México - de León González, Jesús Angel (Universidad de Costa Rica, 1993)
Fifty species (42 genera and 29 families) of marine epibiolie invertebratel wenl found on thomy oylten, Spo1tdyIUl prw,p8 unicolor, froro Puerto Escondido Bay, eastem Baja California Sur, México. These inc1üded